2014
DOI: 10.1016/j.jcat.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Methanol synthesis from CO2 hydrogenation over a Pd4/In2O3 model catalyst: A combined DFT and kinetic study

Abstract: Methanol synthesis from CO 2 hydrogenation on a model Pd/In 2 O 3 catalyst, i.e. Pd 4 /In 2 O 3 , has been investigated using density functional theory (DFT) and microkinetic modeling. Three possible routes in the reaction network of CO 2 + H 2 → CH 3 OH + H 2 O have been examined. Our DFT results show that the HCOO route competes with the RWGS route whereas a high activation barrier blocked the HCOOH route kinetically. The DFT results also suggest that H 2 COO* + H* ↔ H 2 CO* +OH* and cis-COOH* + H* ↔CO* + H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
189
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(201 citation statements)
references
References 77 publications
12
189
0
Order By: Relevance
“…Changes also in the kinetic barriers of the dissociation process cannot be excluded, as reported in the literature, but we could not tackle this point due to the large size of the system. 66,67 However, we recall that the cluster does not wet the surface, 55 and that CO does not stick onto the oxide surface.…”
Section: Resultsmentioning
confidence: 98%
“…Changes also in the kinetic barriers of the dissociation process cannot be excluded, as reported in the literature, but we could not tackle this point due to the large size of the system. 66,67 However, we recall that the cluster does not wet the surface, 55 and that CO does not stick onto the oxide surface.…”
Section: Resultsmentioning
confidence: 98%
“…The adsorbed OH* reacts with H* to obtain H 2 O, and the CO* is desorbed to form CO gas. This reaction pathway can be suppressed by limiting surface COOH formation and thus results in high selectivity toward methanol . Moreover, HCOO* can be hydrogenated to H 2 COO* and H 2 CO*.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the defective In 2 O 3 displayed even better activity for CO 2 hydrogenation to methanol and the reaction followed a mechanism including the cyclic creation and annihilation of oxygen vacancies. They also predicted that the Pd/In 2 O 3 catalyst could be an excellent catalyst for CO 2 hydrogenation to methanol through DFT study . In addition to theoretical studies, there are several experimental studies made for methanol synthesis from CO 2 hydrogenation on In 2 O 3 and In 2 O 3 ‐based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Previous studies have shown that Cu is very selective to convert CO 2 to CH 3 OH by H 2 , and the activity and selectivity can be further promoted by forming alloys or using oxides as supports. [1,[16][17][18][19][20][21][22][23] In comparison, Pt-based catalysts behave differently and are reported to be highly selective to CO [2], which undergoes the reverse-water-gas shift (RWGS) reaction via either carboxyl (*HOCO) or formate (*HCOO) intermediates. [1,[24][25][26] The production of CH 4 is also observed during this process; however, the corresponding selectivity is much lower than that of CO. [2] It is desirable to promote and control the selectivity of a catalyst to convert CO 2 to CO, CH 3 OH or CH 4 .…”
Section: Introductionmentioning
confidence: 99%